Emerging Clinical Features of COVID-19 Related Pancreatitis: Case Reports and Review of the Literature - Fiore, Vito; Beretta, Rosalba; De Vito, Andrea; Barac, Aleksandra; Maida, Ivana; Joeseph Kelvin, David David; Piu, Claudia; Lai, Vincenzo; Madeddu, Giordano; Rubino, Salvatore; Stevanovic, Goran; Korica, Stefan; et al. (Frontiers in Medicine, 2022)
Introduction SARS-CoV-2 is fundamentally a respiratory pathogen with a wide spectrum of symptoms. The COVID-19 related pancreatitis is less considered than other clinical features. The purpose is to describe two cases of pancreatitis associated with COVID-19. Methodology Patients' demographics, clinical features, laboratory, and instrumental findings were collected. Results Two patients admitted to the hospital were diagnosed with COVID-19 and severe acute pancreatitis, according to the Atlanta criteria. Other causes of acute pancreatitis were excluded. Treatment included broad-spectrum antibiotics, proton pump inhibitors, and low molecular weight heparin. Steroids, oxygen, antifungal treatment, and pain killers were administered when appropriate. Both patients were asymptomatic, with normal vital parameters and blood exams, and were discharged in a good condition. Conclusion It is recommendable to include lipase and amylase on laboratory routine tests in order to evaluate the need for the abdominal CT-scan and specific therapy before hospital admission of the patients with COVID-19 related life-threatening acute pancreatitis.